Factors Related to Quality of Life: Correlation Study of Cancer Patients that Received Chemotherapy - Nunung Herlina; Enok Sureskiarti; Maridi Dirjo (GLOBAL HEALTH SCIENCE GROUP, 2021)
The quality of life of cancer patients undergoing chemotherapy is the view of cancer patients undergoing chemotherapy on their lives holistically including physical, psychosocial, spiritual and environmental conditions that are strongly influenced by changes in life due to the effects of cancer itself and the added effects of chemotherapy which is often a complaint in carrying out daily activities. The purpose of this study was to determine the effect of factors related to the quality of life of cancer patients undergoing chemotherapy at Abdul Wahab Sjahranie Hospital Samarinda. The design of this study was descriptive with analytical design in the form of cross sectional. The population is 124 with a sample of 94 respondents. The instrument used in this study is an anket sheet (questionnaire). Univariate and bivariate data analysis using Chi Square. The results of this study using the chi-square test obtained of p value 0.047 (p <0.05) indicating there is a relationship between physical factors and the quality of life of cancer patients undergoing chemotherapy obtained p value of 0,000 (p <0.05) indicating there was a relationship between psychosocial factors and the quality of life of cancer patients undergoing chemotherapy, obtained of p value of 0.396 (p> 0.05) showed no the relationship between environmental factors and the quality of life of cancer patients undergoing chemotherapy, obtained of p value 0.047 (p <0.05) indicating there is a relationship between physical factors and the quality of life of cancer patients undergoing chemotherapy and the p value 0.026 (p< 0.05) indicates a relationship among spiritual factors with the quality of life of cancer patients undergoing chemotherapy at Abdul Wahab Hospital Sjahranie Samarinda. Conclusion: There are relationships between three factors : Physical, Social and Spiritual with Quality of life of cancer patients that received chemotheraphy but one factor : environmental that no relationship.